The degree of doneness affected molecular changes and protein digestibility of pork - Han, Yu; Liu, Hui; Li, Qian; Zhao, Di; Shan, Kai; Ke, Weixin; Zhang, Miao; Li, Chunbao (Frontiers in Nutrition, 2023)
The degree of doneness has been shown to have a great impact on eating quality of meat, however, it is little known whether it affects protein digestibility of meat. In this study, we explored molecular changes and protein digestibility of pork under different degree of doneness. Pork chops were cooked in a 100 ºC water bath for about 26 min and a gradient decrease in doneness was obtained from outer to inner layers of samples. Compared with the raw samples, the cooked samples’ active and total sulfhydryl contents, surface hydrophobicity, and turbidity increased but its solubility decreased. The inner layers with lower doneness contained higher α-helix, and fluorescence intensities of tryptophan and tyrosine residues than the outer layers with higher doneness. The pepsin and pancreatin digestibility of meat proteins in the inner layers were higher than those of the outer layers. Molecular simulation analysis showed that the most abundant protein in pork, i.e., myosin in the outer layers were more stable with an increased number of hydrogen bonds, making it difficult to be digested. These findings provided a new insight into the heterogeneity of meat nutritional quality due to the existence of doneness gradient.